2011
DOI: 10.3324/haematol.2010.035675
|View full text |Cite
|
Sign up to set email alerts
|

The Ph-positive and Ph-negative myeloproliferative neoplasms: some topical pre-clinical and clinical issues

Abstract: including the WNT/beta catenin, notch and hedgehog pathways. Finally, the clinical role of the new JAK2-and BCR-ABL1-inhibitors is considered. Much further progress is likely in several of these areas soon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 145 publications
2
12
0
Order By: Relevance
“…32 Similarly, data using various murine models also support the concept that the level of JAK2V 617 F can initiate and sustain differential MPN phenotypes. 33 Our data reinforce and extend to miRNAs the paradigm that quantitative differences involving the genetic fingerprint may be associated with (or confer) distinct phenotypes (ie, a selflimiting phenotype seen in RT compared with the sustained phenotype associated with ET).…”
Section: Discussionsupporting
confidence: 61%
“…32 Similarly, data using various murine models also support the concept that the level of JAK2V 617 F can initiate and sustain differential MPN phenotypes. 33 Our data reinforce and extend to miRNAs the paradigm that quantitative differences involving the genetic fingerprint may be associated with (or confer) distinct phenotypes (ie, a selflimiting phenotype seen in RT compared with the sustained phenotype associated with ET).…”
Section: Discussionsupporting
confidence: 61%
“…[1][2][3][4] This G.T point mutation causes a valine-to-phenylalanine substitution in position 617 of the protein (V617F) and provides cytokine hypersensitivity to hematopoietic progenitor and stem cells. 5,6 The role of JAK2-V617F in the pathogenesis of MPNs was confirmed in retroviral, transgenic, and knockin mouse models (reviewed in Van Etten et al 7 and Li et al 8 )…”
Section: Introductionmentioning
confidence: 99%
“…17 Thus, TET2 mutations possibly alter hematopoietic stem cell functions and development by epigenetic modifications. 18 However, prognostic impact of TET2 mutations remains controversial, because some studies have suggested a favorable prognostic relevance, whereas others were reporting no significant effect concerning survival in MDS. 12,13,19 Nibourel et al 20 found no significant correlation of the TET2 mutation status with survival outcomes in patients with previously untreated de novo AML who achieved complete remission.…”
Section: Introductionmentioning
confidence: 99%